2017
DOI: 10.1002/jobm.201600618
|View full text |Cite
|
Sign up to set email alerts
|

Lipids of Rhodotorula mucilaginosa IIPL32 with biodiesel potential: Oil yield, fatty acid profile, fuel properties

Abstract: This study analyzes the single cell oil (SCO), fatty acid profile, and biodiesel fuel properties of the yeast Rhodotorula mucilaginosa IIPL32 grown on the pentose fraction of acid pre-treated sugarcane bagasse as a carbon source. The yeast biomass from nitrogen limiting culture conditions (15.3 g L ) was able to give the SCO yield of 0.17 g g of xylose consumed. Acid digestion, cryo-pulverization, direct in situ transesterification, and microwave assisted techniques were evaluated in comparison to the Soxhlet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 35 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…Li et al [57] confirmed that R. muciloginosa TJY15a constitute a good feedback for biodiesel production. Arora et al [59] and Khot and Ghosh [65] reported, respectively, the same conclusion for C. minutissima cultivated in optimal condition of lipid productivity (N L P L ) and for the oleaginous yeast R. mucilaginosa IIPL32.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…Li et al [57] confirmed that R. muciloginosa TJY15a constitute a good feedback for biodiesel production. Arora et al [59] and Khot and Ghosh [65] reported, respectively, the same conclusion for C. minutissima cultivated in optimal condition of lipid productivity (N L P L ) and for the oleaginous yeast R. mucilaginosa IIPL32.…”
Section: Resultsmentioning
confidence: 60%
“…[30]; Chlorella minutissima [60]; Mortierella isabellina [61], Y. lipolytica in POME [62], R. mucilaginosa [63] and L. starkeyi [64]. Khot and Ghosh [65] found a similar result for the strain R. mucilaginosa IIPL32. Brar et al report that the fatty acid profile of wild Trichosporon sp.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Sugarcane bagasse, sugar cane husk, wheat straw, rice straw and corn stover are the most promising non-edible lignocellulose biomasses/feedstocks in U.S.A, Asia, and Europe [70][71][72]. Recently, Rhodotorula mucilaginosa IIPL32 grown on the pentose fraction of acid pretreated sugarcane bagasse as a carbon source synthesized 15.3 g/l biomass along with 0.17 g single cell oil as per g of xylose consumed [73]. Certain oleaginous yeast such as Cystobasidium oligophagum JRC1 is capable of cellulase and lipase production simultaneously when grown on a wide range of substrates including carboxymethylcellulose (CMC) and accumulated 36.46% (w/w) lipid on the medium with CMC as sole carbon source [74].…”
Section: Low-cost Substrates Utilized By Oleaginous Yeasts To Producementioning
confidence: 99%